Histopathological Typing and Topographic Distribution of Head and Neck Lesions: An Eight Year Retrospective Study - Fatima Iqbal, Saleha Saeed, Nasiha Bashir, Sana Mushtaq Khattak, Tehmina Naushin, Muhammad Sulaiman (Journal of Rawalpindi Medical College, 2021)
Objective: To analyze the histopathological pattern of head and neck lesions with respect to demographic findings referred to the histopathology lab of Peshawar Medical College (PMC). Study Design: Descriptive cross-sectional study. Place and Study duration: Histopathology laboratory of PMC, Peshawar, Pakistan. Jan 2010 to Dec 2018. Materials and Methods: A retrospective study was conducted on a total of 743 specimens submitted to the histopathology lab for diagnosis. Variables like age, gender, site, and histopathological spectrum were evaluated. Statistical Package for Social Sciences (SPSS) version 19 was used for descriptive and inferential statistics considering p-value ≤0.05 significant. Results: In our study <30 age group was common for head and neck lesions. Females were frequently affected than males. A maximum number of diagnosed lesions was benign in nature with goiter as the most common lesion. Oral squamous cell carcinoma (OSCC) was a widespread malignant neoplasm. According to the site, the thyroid showed 36%of lesions followed by 9.5% lip and oral cavity and lymph nodes respectively. Conclusion: This study concluded a variety of head and neck lesions with respect to age, gender, and site in our region that can help in improved understanding, management, and control of the disease.